A simulator of the MAJIS instrument onboard the JUICE mission: Description and application to operational and scientific cases - C. Royer; P. Haffoud; Y. Langevin; F. Poulet; D. Bockelée-Morvan; E. D’Aversa; M. Cisneros-González; D. Grassi; N. Ligier; G. Piccioni; J. Carter; F. Tosi; et al. (Planetary and Space Science, 2025)

Current applications of benchtop FT-NMR in food science: From quality control to adulteration detection - Giacomo Di Matteo; Silvia Grassi; Maria Carmela Emanuele; Giuseppe Scioli; Federico Ivan Brigante; Luana Bontempo; Cinzia Ingallina; Claude Guillou; Anatoly P. Sobolev; Luisa Mannina (Food Research International, 2025)

Elucidating mechanisms of action of environmental contaminants from Doce River in Brazilian fish embryos using metabolomics and chemometric methods - Flávia Y. Yamamoto; Larissa A. Batista; Mayara P. Santos; Carmen Bedia; Silvia Lacorte; Rivelino M. Cavalcante; Marco T. Grassi; Denis M. de Souza Abessa; Romà Tauler (Science of The Total Environment, 2025)

nano-TiO2 reduces bioavailability and biotransformation responses to crude oil WAF-associated PAHs in the European sea bass Dicentrachus labrax - M.L. Vannuccini; C. Della Torre; G. Grassi; C. Zambonin; P. Cotugno; M.J. Leaver; I. Corsi (Marine Pollution Bulletin, 2024)

Conversion of foliar residues of Sansevieria trifasciata into adsorbents: dye adsorption in continuous and discontinuous systems - Patrícia Grassi; Matias Schadeck Netto; Sérgio Luiz Jahn; Jordana Georgin; Dison S. P. Franco; Mika Sillanpää; Lucas Meili; Luis F. O. Silva (Environmental Science and Pollution Research, 2022)

Novel application of FeIn2S4 as an efficient photo-Fenton catalyst for degradation of Ponceau 4R in aqueous solution - P. Grassi; J. da Silveira Salla; S. L. Jahn; E. L. Foletto (International Journal of Environmental Science and Technology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Association between high proviral load, cognitive impairment, and white matter brain lesions in HTLV-1-infected individuals - Rosangela Souza Kalil; Isabelle Vasconcellos; Carolina Rosadas; Andrea Cony; Dulcino P. Lima; Cassia C. Alves Gonçalves; Everton Batista; Maria Fernanda Grassi; Bernardo Galvão-Castro; Graham P.Taylor; Marzia Puccioni-Sohler (Journal of NeuroVirology, 2021)

Association of CHRNA5 Gene Variants with Crack Cocaine Addiction - Angelita P. Aroche; Diego L. Rovaris; Eugenio H. Grevet; Anderson R. Stolf; Breno Sanvicente-Vieira; Felix H. P. Kessler; Lisia von Diemen; Rodrigo Grassi-Oliveira; Claiton H. D. Bau; Jaqueline B. Schuch (NeuroMolecular Medicine, 2020)

Potential of Cedrella fissilis bark as an adsorbent for the removal of red 97 dye from aqueous effluents - Jordana Georgin; Dison S. P. Franco; Patricia Grassi; Denise Tonato; Daniel G. A. Piccilli; Lucas Meili; Guilherme L. Dotto (Environmental Science and Pollution Research, 2019)

Geophysical surveys to study a landslide body (north-eastern Sicily) - S. Imposa; S. Grassi; F. Fazio; G. Rannisi; P. Cino (Natural Hazards, 2017)

Placental aging and oxidation damage in a tissue micro-array model: an immunohistochemistry study - Ambrogio P. Londero; Maria Orsaria; Stefania Marzinotto; Tiziana Grassi; Arrigo Fruscalzo; Angelo Calcagno; Serena Bertozzi; Nastassia Nardini; Enrica Stella; Ralph J. Lellé; Lorenza Driul; Gianluca Tell; et al. (Histochemistry and Cell Biology, 2016)

Gokyo Khumbu/Ama Dablam Trek 2012: effects of physical training and high-altitude exposure on oxidative metabolism, muscle composition, and metabolic cost of walking in women - E. Tam; P. Bruseghini; E. Calabria; L. Dal Sacco; C. Doria; B. Grassi; T. Pietrangelo; S. Pogliaghi; C. Reggiani; D. Salvadego; F. Schena; L. Toniolo; et al. (European Journal of Applied Physiology, 2016)

Placental hCG immunohistochemistry and serum free-Beta-hCG at 11–13 weeks’ gestation in intrauterine fetal demise - Ambrogio P. Londero; Maria Orsaria; Tiziana Grassi; Angelo Calcagno; Stefania Marzinotto; Maria Ceraudo; Arrigo Fruscalzo; Lorenza Driul; Laura Mariuzzi (Histochemistry and Cell Biology, 2013)

Fire in the Air: Biomass Burning Impacts in a Changing Climate - Melita Keywood; Maria Kanakidou; Andreas Stohl; Frank Dentener; Giacomo Grassi; C. P. Meyer; Kjetil Torseth; David Edwards; Anne M. Thompson; Ulrike Lohmann; John Burrows (Critical Reviews in Environmental Science and Technology, 2013)

The European carbon balance. Part 4: integration of carbon and other trace‐gas fluxes - E. D. SCHULZE; P. CIAIS; S. LUYSSAERT; M. SCHRUMPF; I. A. JANSSENS; B. THIRUCHITTAMPALAM; J. THELOKE; M. SAURAT; S. BRINGEZU; J. LELIEVELD; A. LOHILA; C. REBMANN; et al. (Global Change Biology, 2010)

The European carbon balance. Part 4: integration of carbon and other trace‐gas fluxes - E. D. SCHULZE; P. CIAIS; S. LUYSSAERT; M. SCHRUMPF; I. A. JANSSENS; B. THIRUCHITTAMPALAM; J. THELOKE; M. SAURAT; S. BRINGEZU; J. LELIEVELD; A. LOHILA; C. REBMANN; et al. (Global Change Biology, 2010)
Overviewing the European carbon (C), greenhouse gas (GHG), and non‐GHG fluxes, gross primary productivity (GPP) is about 9.3 Pg yr −1 , and fossil fuel imports are 1.6 Pg yr −1 . GPP is about 1.25% of solar radiation, containing about 360 × 10 18 J energy – five times the energy content of annual fossil fuel use. Net primary production (NPP) is 50%, terrestrial net biome productivity, NBP, 3%, and the net GHG balance, NGB, 0.3% of GPP. Human harvest uses 20% of NPP or 10% of GPP, or alternatively 1‰ of solar radiation after accounting for the inherent cost of agriculture and forestry, for production of pesticides and fertilizer, the return of organic fertilizer, and for the C equivalent cost of GHG emissions. C equivalents are defined on a global warming potential with a 100‐year time horizon. The equivalent of about 2.4% of the mineral fertilizer input is emitted as N 2 O. Agricultural emissions to the atmosphere are about 40% of total methane, 60% of total NO‐N, 70% of total N 2 O‐N, and 95% of total NH 3 ‐N emissions of Europe. European soils are a net C sink (114 Tg yr −1 ), but considering the emissions of GHGs, soils are a source of about 26 Tg CO 2 C‐equivalent yr −1 . Forest, grassland and sediment C sinks are offset by GHG emissions from croplands, peatlands and inland waters. Non‐GHGs (NH 3 , NO x ) interact significantly with the GHG and the C cycle through ammonium nitrate aerosols and dry deposition. Wet deposition of nitrogen (N) supports about 50% of forest timber growth. Land use change is regionally important. The absolute flux values total about 50 Tg C yr −1 . Nevertheless, for the European trace‐gas balance, land‐use intensity is more important than land‐use change. This study shows that emissions of GHGs and non‐GHGs significantly distort the C cycle and eliminate apparent C sinks.

Special Contribution: An Overview of Recent Seismic Refraction Experiments in Central Europe - A. Guterch; M. Grad; A. Špičák; E. Brückl; E. Hegedüs; G.R. Keller; H. Thybo; K. Aric; S. Acevedo; I. Asudeh; M. Behm; A. A. Belinsky; et al. (Studia Geophysica et Geodaetica, 2003)

Magnetic analysis of human brain tissue - Paola P. Schultheiss-Grassi; Jon Dobson (BioMetals, 1999)